2015
DOI: 10.1007/s10620-014-3508-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Location of Pathology Is Predictive of Prolonged Fluoroscopy Time During ERCP: A Multicenter American Study

Abstract: Prolonged FT during ERCP is associated most strongly with intrahepatic cases. FT can be used most effectively as a quality measure if it is stratified according to presence or absence of intrahepatic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…During ERCP, the patient is exposed to the primary beam and consequently receives a higher radiation dose compared to endoscopy staff, whose major source of radiation exposure is caused by scattered radiation from the patient [6]. Over the years, both the number and the complexity with associated increased technical difficulty of therapeutic ERCP procedures have significantly increased resulting in longer procedural [7] and fluoroscopy times [8,9]. Prolonged fluoroscopy time to the same skin area, irradiation through thick body masses as well as an extensive use of high-dose rate modes may produce a high radiation dose to the patient's skin and increase the risk of radiation-induced skin injury [10,11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During ERCP, the patient is exposed to the primary beam and consequently receives a higher radiation dose compared to endoscopy staff, whose major source of radiation exposure is caused by scattered radiation from the patient [6]. Over the years, both the number and the complexity with associated increased technical difficulty of therapeutic ERCP procedures have significantly increased resulting in longer procedural [7] and fluoroscopy times [8,9]. Prolonged fluoroscopy time to the same skin area, irradiation through thick body masses as well as an extensive use of high-dose rate modes may produce a high radiation dose to the patient's skin and increase the risk of radiation-induced skin injury [10,11].…”
mentioning
confidence: 99%
“…Previously, it has been found that the type of x-ray unit, anatomical location of pathology, difficult cannulation, annual volume and experience of endoscopist, trainee involvement, complexity of procedure, sphincterotomy, stent insertion, balloon dilatation, stone extraction, and other interventions influenced on the exposure levels in ERCP [8,9,[14][15][16][17][18][19][20][21][22]. A randomized trial by Uradomo et al [22] showed that a Decreasing the distance between the endoscopy and fluoroscopy screens in the ERCP was also found to reduce a fluoroscopy time by 1.4 minutes [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each procedure has been reported to be associated with different radiation doses, and the difficult procedures require more radiation exposure. 2,8,13,[16][17][18][19][20] In these studies, difficult or time-consuming procedures include pancreatic sphincterotomy, 13,20 balloon dilatation, 13,18,20 and biliary or pancreatic drainage, 13,18,19 which were incorporated into our model. In-hospital ERCP, which has not been reported in previous studies, also requires more radiation because it is an index or difficult procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Because the results of fluoroscopy parameters, especially fluoroscopy times, were no different between the two groups and were comparable with other studies 26 27 , there was low bias for the fluoroscopy control in this study. Second, we excluded complex cases, especially hilar cholangiocarcinoma, because of the need for an antero-posterior view of fluoroscopy, as those indications might require a longer fluoroscopy time and result in greater radiation exposure 5 28 . We then calculated an equivalent dose rate to eliminate variation in fluoroscopy time and this might be appropriate for radiation monitoring rather than the mean dose per procedure 17 .…”
Section: Discussionmentioning
confidence: 99%